Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

The Implementation of Provisions of IFRS Framework and Financial Perfomance of Banks - Anichebe, Alphonsus Sunday; Okpala, Ngozi Eugenia (International Journal of Trend in Scientific Research and Development, 2018)
The need for global financial language gave birth to International Financial Reporting Standards (IFRS). The adoption of IFRS has been argues to have changed the manner in which the financial statements are prepared, presented and reported. IFRS represents a single set of high quality, globally accepted accounting standards that can enhance comparability of financial reporting across the globe. The significant disparities between the Nigerian Statement of Accounting Standards and International Financial Reporting Standards have resulted in the Statement of Accounting Standards being regarded as outdated and incomplete as an authoritative and internationally accepted guide to the preparation of financial statements. The study however examined the extent to which Nigerian banks have implemented the provisions of IFRS frameworks. The sample comprises of fourteen quoted deposit money banks in Nigeria. Specifically, financial statement figures of 2007 – 2011 (pre-adoption period) and 2012 – 2016 (post-adoption period) were utilized. The study adopted the ex-post facto research design. Annual panel data were collected from the financial statements and accounts of 14 deposit money banks quoted on the Nigerian Stock Exchange as well from the Securities and Exchange Commission statistical bulletin from 2007 to 2016. The findings revealed that the return on shareholders’ funds has improved since implementation of International Financial Reporting Standards (IFRS) on Nigerian banks. IFRS implementation has significant effect on the profitability of quoted banks in Nigeria. The implementation of International Financial Reporting Standards (IFRS) has significantly influenced banks’ earnings and it was concluded that IFRS has positive impact on equity and earnings of banks. It was recommended that government and regulatory authorities should organize more quality training to get bankers informed.
Keywords: Banks; Financial performance; IFRS

Contractual capacity and the conflict of laws in common-law jurisdictions (part 1) : the United Kingdom - Fredericks, Eesa A. (Obiter, 2018)
This series of two articles provides a comparative overview of the position in the common-law conflict of laws in respect of the contractual capacity of natural persons. The comparative study is undertaken in order to provide guidelines for the future development of South African private international law. Reference is primarily made to case law and the opinions of academic authors. The legal position in the law of the United Kingdom, as the mother jurisdiction in Europe, is investigated in part I. Although Scotland is a mixed civil/common-law jurisdiction, the situation in that part of the United Kingdom is also discussed. Part II will deal with the rules and principles of private international law in respect of contractual capacity in Australasia (Australia and New Zealand), North America (the common-law provinces of Canada and the United States of America), Asia (India, Malaysia and Singapore) and Africa (Ghana and Nigeria). Part II also contains a comprehensive summary of the legal position in the common-law countries, followed by ideas for the reform of South African private international law in this regard.

The regulation of non-standard employment in Southern Africa : the case of South Africa with reference to several other SADC countries - Mokofe, William Manga (University of South Africa, 2018)
This doctoral thesis deals with the regulation of non-standard employment in Southern Africa: the case of South Africa with reference to several other SADC countries. The growth and presence of non-standard employment since the 1970s has revealed an important concern in a number of countries, both at the global and national levels. The overall significance of non-standard employment has increased in recent decades in both developed and developing states, as its use has grown exponentially across economic sectors and employment. Non-standard employment is the opposite of the standard employment relationship, which is work that is full time and indefinite. Non-standard employment includes an unequal employment relationship between an employee and an employer. Some workers choose to work in non-standard employment, and the choice has positive results. Nonetheless, for the majority of workers, non-standard employment is associated with job insecurity, exploitation, and the absence of trade unions and collective bargaining. Non-standard employment can also create challenges for firms, the labour market and the economy, including society at large. Backing decent work for all entails a comprehensive understanding of non-standard employment and its ramifications. This study explores the regulation and protection of non-standard employment in Southern Africa with focus on South Africa. The study draws on international and regional labour standards, the South African Constitution of 1996, and the national experience to make policy recommendations that will ensure workers are protected, firms are sustainable and labour markets operate well. Social justice and the democratisation of the workplace cannot be achieved if workers in non-standard employment are excluded from the labour relations system.
Keywords: Collective bargaining; Labor laws and legislation; Non-standard employment; Part-time employment; South Africa; Standard employment; Temporary employment; Temporary workers; Vulnerable workers

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Business combinations and group of companies : perspectives from accounting, law and corporate finance - Coda, Stefano (Université Paris 1, 2018)
Dans le cadre général des regroupements d'entreprises et des groupes de sociétés, cette thèse porte sur des questions d'intérêt à la croisée de la comptabilité, du droit (notamment les dispositions légales et la réglementation comptable) et de la finance d'entreprise. En ce qui concerne la théorie comptable, le chapitre 2 étudie comment les chercheurs en économie d'entreprise ont compris les groupes d'entreprises, les comptes de groupe et le processus de leur préparation, en particulier par rapport aux juristes italiens. Ensuite, le chapitre 3 reconstruit le processus politique et législatif qui a engendré la naissance du concept de groupe de sociétés dans le corpus juridique italien.Concernant le droit et la politique comptable, une analyse comparative est effectuée au chapitre 4qui montre clairement l'évolution de la notion de contrôle et de son utilisation dans les comptes consolidés (comptes de groupe) et les regroupements d'entreprises (I) en droit européen, (II) selon les normes comptables internationales publiées par l'IASB (International Accounting Standards Board) et (III) par rapport aux principes comptables généralement admis aux États-Unis («USGAAP»). De plus, les chapitres 5 et 6 étudient les effets du lobbying sur les normes comptables concernant les états financiers consolidés et les regroupements d'entreprises publiés par l'IASB. Fait intéressant, les résultats concordent avec une forme de capture du normalisateur comptable international par une catégorie d'institutions financières. En effet, confrontées à un modèle de consolidation prétendument basé sur le contrôle, ces dernières ont plaidé en faveur d'une exception de consolidation fondée sur un modèle de propriété et documentée comme ayant été proposée par les sociétés d'audit américaines dans ce contexte au moins depuis 1995. Ce modèle s’avère avoir trouvé un terrain fertile au sein de l'IASB. En conséquence, d'autres catégories d'institutions financières,telles que les fonds d'investissement à long terme et ceux gérés par une famille tout en préférant un modèle de consolidation différent, ne sont plus autorisées à présenter des états financiers consolidés. En ce qui concerne la finance d’entreprise, le chapitre 7 analyse les implications de différentes décisions de financement dans un nouveau échantillon de fusions et acquisitions entre institutions financières (banques et assurances) consommées dans le monde entier au cours des deux dernières décennies. En particulier, il étudie (I) la relation entre la méthode de choix de paiement (si le prix est payé en cash, en actions ou une combinaison des deux) et le choix du mode de financement d'un regroupement d'entreprises (y compris les instruments hybrides) et (II) la réaction des investisseurs à l'annonce de la combinaison. En ce qui concerne ce dernier point, l'utilisation de deux tests non paramétriques permet de détecter une relation intéressante entre la réaction du marché à l'annonce et les différents modes attendus de financement de la transaction.
Keywords: Accountings standard setting; Comptabilité; Consolidation exemption; Egroupements d'entreprises; Finance d'entreprise; Finances; Financial institutions; Gestion d'entreprise; Groupes de sociétés; IASB; IFRS 10; IFRS 3; Mergers and acquisitions; Method of payment; Politics; Politique comptable; Sources of fundings; Économie d'entreprise

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Relations between quality of trademarks and cognitive and conative variables of consumers - Naumovski, Goce (Université de Strasbourg, 2018)
But de la recherche : déterminer la dépendance des caractéristiques des marques (perceptibilité visuelle, représentation graphique, le caractère distinctif, non-généricité etc.), sur les types généraux spécifiques de capacités intellectuelles et sur les caractéristiques conatives des consommateurs de la population générale, par application de nombreux tests. La recherche a été réalisée sur un échantillon de 206 sujets-consommateurs. Ils ont évalué la qualité des marques de commerce (déposées et refusées) pour différents types de produits et services (TM-1 test). Les sujets ont été testés avec 3 tests cognitifs et 6 tests conatifs. Méthodes quantitatives appliquées : paramètres élémentaires de la statistique descriptive ; corrélation ; analyse factorielle ; analyse de régression multivariée, analyse canonique des corrélations. Les résultats ont indiqué que les variables cognitives et conatives ont des relations statistiquement significatives avec les résultats de TM test (qualité des marques).
Keywords: Capacités cognitives; Caractéristiques conatives; Cognitive abilties; Comportement des consommateurs; Conative characteristics; Consommateur; Consumers; Intellectual property; Marques; Marques de commerce (droit international); Propriété intellectuelle (droit international); Trademarks

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.

Trade Openness and Financial Development in Sub Saharan Africa: The Role of Institutional Quality - Abeka, Mac Junior (University of Cape Coast, 2018)
The financial development of many Sub-Saharan African countries over the years has not been able to match up with other regions like the Middle East and North Africa, East Asia and Pacific, and Europe and central Asia (IMF, 2016). Trade openness has been argued in several empirical literature as a factor that could spur up the level of financial development, although the high levels of trade openness in Sub-Saharan Africa is not contributing much to the desired levels of financial development in Sub-Saharan Africa. However, there is an indication in literature that trade openness will be more relevant to financial development of economies that have a strong institutional quality. Thus, by using system General Method of Moment estimation technique, this study examined how institutional quality moderates the relationship between trade openness and financial development of Sub-Saharan African economies. The study found that institutional quality enhances the effect of trade openness on financial development of Sub-Saharan African economies. It is therefore recommended that, Sub-Saharan African economies should put in measures to strength their institutional quality so that the high levels of trade openness will better enhance financial development. Specifically, trade openness can better enhance financial development by improving government effectiveness, reducing corruption, enhancing regulatory quality, abiding by the rule of law, and allowing voice and accountability. As an extra benefit, the improvements in institutional quality on their own too will yield positive impact on financial development.

Effect of IFRS on Value Relevance of Accounting Information: Evidence from Quoted Manufacturing Firms in Nigeria - Ezejiofor, Raymond Asika (International Journal of Trend in Scientific Research and Development, 2018)
This study evaluated the extent to which value relevance of financial information in Nigerian manufacturing firms has improved after the implementation of International Financial Reporting Standards (IFRS). Specifically, the study intended to: Ascertain the extent the adoption of IFRS has significantly improved the book value per share of manufacturing companies in Nigeria; Determine the extent the adoption of IFRS has significantly improved the Earnings Per Share of manufacturing companies in Nigeria and Examine the extent the adoption of IFRS has significantly improved the cash flow of manufacturing companies in Nigeria. Ex-post facto research design was adopted for the study. A sample of 54 manufacturing companies was randomly selected from manufacturing companies quoted on the Nigerian Stock Exchange for the periods of 2008-2015. Data for the study were obtained from the annual reports and accounts of the sampled companies. Specifically, a modified price model for detecting value relevance of accounting data for two different periods was employed. Regression Analysis and Chow test statistical tools were used to analyze and validate the data with aid of SPSS version 20.0. The study found that the adoption of IFRS has improved the book value per share, market share price, Earnings Per Share and cash flow of manufacturing companies in Nigeria. The implication of findings is that the value relevance of accounting information of manufacturing companies is more sensitive during Post-IFRS era than the Pre-IFRS era. The findings also imply that the book value per share, market price, earnings and cash flow have become informative to equity investors in determining the value of firms following IFRS adoption. The study recommends among other things that the accounting information for book value per share should be communicated to the investing public; and such information should be of high quality to avoid negative consequences on the part of investors.
Keywords: Accounting information; Manufacturing company; Value relevance

Impact of Contractual Capacity of Minor - Godha, Atisha (International Journal of Trend in Scientific Research and Development, 2018)
A contract involves s a promise between two persons for the exchange of either good or services. A contract signifies the free consent of the parties to the contract to be bound by law. For a contract to be valid, it must have these basic elements: mutual assent, consideration, capacity, and legality. Mutual assent is characterized by offer and acceptance through mutual accent; "consideration," on the other hand denotes any form of compensation with something of value for the goods or services traded. A contract between persons, either natural persons or legal persons, who have no capacity to contract can either be voidable or void depending on the case. Legality gives the condition that should be satisfied for a contract to be excised by the law. Illegal contracts are for example those involving illegal activities. For example one can't bring a plea of damages to a court of law for breach of a contract entered into to kill another person.The possible remedies for breach of contract are; general damages, consequential damages, reliance damages, and specific performance. This paper will examine the capacity to contract as pertains to contracts entered by minors minor's.
Keywords: Capacity; Consideration; Contract; Legality; Minor; Mutual accent void/voidable

Aspects of the regulation of cross-border insolvency in South Africa - Chitimira, Howard (Obiter, 2018)
This article analyses the regulation of cross-border insolvency under the Cross-Border Insolvency Act 42 of 20001 in order to examine the adequacy of such regulation as regards to the enforcement of insolvency proceedings in South Africa and other relevant jurisdictions. To this end, the paper provides an overview analysis of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act. Moreover, where possible, the paper also provides a comparative analysis of selected aspects of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act and those that are provided under the Insolvency Act 24 of 1936 and other related international instruments. This is done to expose the challenges and future prospects of the regulatory and enforcement framework under the Cross-Border Insolvency Act in South Africa.
Keywords: Insolvency; Regulation; South Africa

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

International Arbitration Practices in Nigeria: A Construction Industry Appraisal - Ewa, O. O.; Haytham, B.; Okon, E. E.; Enang, O. P.; Emiri, D. A. (World Journal of Innovative Research, 2018)
This paper aims to investigate Corporate Alternative Conflict Management and Dispute Resolution compliance through an appraisal of International Arbitration practices in Project-based Organizations in the Nigerian Construction Industry. In this study, simple percentages and frequencies of occurrence were used to analyse data derived through subject matter interviews and a questionnaire survey. Using the Survey Monkey tool, 85 questionnaires were distributed to key players in the AEC (Architecture-Engineering-Construction) Industry including Engineers, Project Managers, Architects and Quantity Surveyors and 53 were returned complete. The survey indicated that 66% preferred a more private Construction Arbitration to a public Litigation as a preferred method of dispute resolution, with 65% agreeing that a lack of proper project funding hinders the arbitration process in the Nigerian Construction Industry. 66% agree that Arbitration Time contributes more to project delays while 32% believe that Cost of the arbitration process is the greater source of project delays. We recommend that issues of confidentiality be carefully managed in dealing with outside counsels, while Project-based Organisations in Nigeria should ensure to develop master plans compatible with long-term strategies, including setting aside adequate funding for the timely resolution of project disputes through the implementation of only Arbitration-friendly contracts. This paper contributes to knowledge by bringing to bear the current compliance levels of project-based organisations in the practice of Arbitration in the Nigerian Construction Industry.

A comparative study of the effects of liquidation or business rescue proceedings on the rights of the employees of a company - Joubert, Engela Petronella (University of South Africa, 2018)
Whenever legal disciplines overlap interesting scenarios occur and differences in opinions create intellectual tension. One such interesting scenario occurs when employees’ rights are affected during a company’s liquidation or business rescue. The employees of a company are normally the last persons to find out that a company is struggling financially. They are also the only stakeholders who are in no position to negotiate their risk should the company be liquidated. It is therefore necessary to evaluate the rights given to employees during a company’s liquidation and business rescue. The fundamental ideologies of company law, insolvency law and labour law are challenged and examined to attempt a harmonizing result that respects the core of each discipline. It is crucial to determine whether an appropriate balance is struck between the interests of all the stakeholders of the company during these procedures. The aim of this thesis is to evaluate whether South Africa manages to strike this balance. If employee rights are protected whilst a company is restructured back to solvency and success, this balance will be struck. An evaluation will also be made whether employees are always better protected during business rescue than in liquidation. The study analyses employee rights in a company’s liquidation and during a company’s restructuring process. The comparative study of employee rights in liquidation and rescue is done with the jurisdictions of Australia and England – countries with similar procedures. Important conclusions show that South Africa protects employee rights during business rescue procedures the best. An appropriate balance is indeed struck between the interests of all stakeholders of a company during business rescue procedures and employees are most of the time better off after a restructuring than in a liquidation. Should the recommendations for law reform be implemented in our legislation, South Africa will overcome the few obstacles currently in its way to be seen as a world leader where employee rights are concerned in liquidation proceedings as well as business rescue.
Keywords: Australia; Bankruptcy; Business rescue; Corporate reorganizations; Employee rights; Employment contract; Great Britain; Liquidation; Ranking of claims; South Africa

Combating corruption in public procurement in developing countries : a legal analysis - Mugadza, W. T. (North-West University, 2018)
This study was motivated by the quest to find new innovative and practical ways of combating public procurement corruption in developing countries to complement the existing measures. This was achieved by comparing three jurisdictions, Hong Kong-China, Botswana and South Africa. The focus was on how each jurisdiction uses the following four measures to curb public procurement corruption: criminal measures; administrative measures; institutional measures and civil activism measures. It was established that Hong Kong uses what this study has classified as the traditional approach of combating public procurement corruption. The traditional approach is characterised by the use of a separate procurement legal framework and a separate corruption legal framework to curb public procurement corruption. Its strengths are in the strict enforcement of criminal measures that are anchored on a robust legal framework, a clear anti-corruption strategy, an independent anti-corruption agency (institutional measure), effective internal oversight and a strong political will. However, the following weaknesses of the traditional approach were identified: over reliance on criminal measures; excessive dependence on one enforcement institution; it neglects the development of administrative measures and has weak civil activism measures. It was established that Botswana uses what this study has classified as the classical approach of combating public procurement corruption. The classical approach is characterised by a procurement legal framework that incorporates very minimum anti-corruption provisions. The anti-corruption provisions in the procurement legislation are enforced by an external institution (the DCEC in the case of Botswana) which relies heavily on the criminal measures. Its strengths are the following: a strong legal framework which provides for a clear anti-corruption strategy; it has anti-corruption units in each Ministry and it has a dedicated Corruption Court. However, the classical approach has the following weaknesses: the anti-corruption agency is not adequately independent as it under the control of the executive (the President in the case of Botswana); lacks effective internal oversight mechanisms; weak political will; neglects the development of administrative measures and civil activism measures are almost non-existent save for the media. It was established that South Africa uses what this study has classified as the traditional cum silo approach of combating public procurement corruption. The traditional cum approach is characterised by multiple procurement legislation which has certain but minimum anti-corruption provisions and a separate corruption legal framework. Multiple anti-corruption agencies are prone to political interference which renders them ineffective and unfit for purpose. Its strength is in the promotion and protection of civil activism measures (right to access information, right to freedom of speech and legal protection of whistle-blowers). Notable weaknesses of the traditional cum silo approach are: the poor enforcement of criminal measures; there is no lead anti-corruption agency that spearheads and coordinates all cases of public procurement corruption; there is no clear anti-corruption strategy; the administrative measures such as debarment are poorly enforced; it has multiple anti-corruption institutions that lack focus and professionalism which results in political manipulation. The thesis concluded by suggesting a new approach, the contemporary approach to combating public procurement corruption which entails the enactment of a single procurement legislation (model law) the Public Procurement and Combating of Public Procurement Corruption Act (hereafter PPCPPC). The contemporary approach advocates for the regulation of public procurement and the combating of public procurement corruption in one legislation. This legislation (PPCPPC) takes into account, the current demands for public procurement as well as future developments of public procurement. These include but are not limited to self-cleaning, cyber-crime and public procurement corruption as well as the role of foreign convictions for debarment purposes. The envisaged PPCPPC will in addition to regulating public procurement, encompass the best criminal measures, administrative measures, institutional measures and civil activism measures. In addition, the contemporary approach through the PPCPPC proposes two new innovations: the corruption clearance certificate and a mandatory anti-corruption clause in all government contracts.
Keywords: Accountability; Administrative measures; Anti-corruption clause; Botswana; Civil activism measures; Classical approach; Combating corruption; Competitiveness; Contemporary approach; Corruption clearance; Criminal measures; Debarment; Equality; Fairness; Hong Kong; Institutional measures; Integrity; Procurement principles; Public procurement; South Africa; Traditional approach; Transparency; Value for money

Who is in? Who is out? How the Uncitral Transparency Rules Can Influence the Upcoming Amendments of the ICSID Arbitration Rules - Yu, Hong-Lin (Contemporary Asia Arbitration Journal, 2018)
The International Center for Settlement of Investment Disputes (hereinafter "ICSID") has started its fourth amendment of its Arbitration Rules since 2016. The issue of transparency has been highlighted as a delicate issue in ICSID ongoing current amendment. It is also listed in the topics that have been identified for potential amendment. This article analyses how the issues of access to hearings and confidentiality over information arising from arbitration is treated under the current framework. A comparison is made against the Transparency Rules. The analysis is also made against the comments received from the public whose views are analysed as a possible direction the amendment may take.

L’arbitrage international dans l'OHADA : évolution vers l’arbitrage des investissements en Afrique - Dalil, Mustapha (Journal of Strategic Affairs, 2018)
En vertu des dispositions de l’article 53 Al. 1 du Traité de création de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires) : « Le présent traité est, dès son entrée en vigueur, ouvert à l’adhésion de tout Etat membre de l’Union Africaine et non signataire du traité. Il est également ouvert à l’adhésion de tout autre Etat non membre de l’Union Africaine invité à y adhérer du commun accord de tous les Etats Parties ». Cette action d’harmonisation du droit des affaires, tout en s’inspirant d’autres législations telles que le droit français et la common law, les Etats-membres de l’OHADA ont à leur disposition un arsenal législatif efficace et approprié à leur développement économique communautaire. Ce droit revêt un intérêt particulier pour les entreprises marocaines actives dans l’espace OHADA. Le Maroc, par le renouvellement de son adhésion à l’Union Africaine (UA) et en procédant à une demande d’adhésion à la Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) dont le but est de « promouvoir la coopération et l’intégration dans la perspective d’une Union économique de l’Afrique de l’Ouest », (le Maroc) a réaffirmé sa détermination d’intégrer les espaces économiques africains de référence
Keywords: Arbitrage international; Droit des affaires; Développement économique; Relations internationales; Union africaine; الاتحاد الإفريقي; التحكيم الدولي; التنمية الاقتصادية; العلاقات الدولية; قانون الأعمال

The realisation of rights in terms of the Consumer Protection Act 68 of 2008 - Scott, Tshepiso (University of South Africa, 2018)
The thesis examines the enforcement of consumer rights in South Africa, and is set against the backdrop of the underlying principles and theories on the enforcement of consumer protection law. It then analyses the various forms of consumer protection law enforcement mechanisms that were in place prior to the implementation of the Consumer Protection Act 68 of 2008, and sets out why there was a need for the enactment of the Consumer Protection Act. The thesis then critically discusses the consumer protection law enforcement mechanisms introduced and/or catered for by the Consumer Protection Act. The in-depth comparative analysis against the consumer protection law enforcement dispensations in both India and the United Kingdom culminates in a critical analysis of the successes and shortcomings of consumer protection law enforcement regime in present-day South Africa; as well as recommendations (in the form of legislative amendments and practical solutions) on how the South African consumer protection enforcement framework can be improved in order to facilitate the realisation of consumer rights.
Keywords: Consumer protection; Consumer rights; Enforcement mechanisms

Internet regulation and development: the battle over the network neutrality - Melo, Lílian Manoela Monteiro Cintra de (Universidade de São Paulo, 2018)
We have arrived at crossroads in the debates about the future of the internet governance. It is high time to address the reasons why policy choices have not been sufficient to preserve the internet\'s promise to bring about development, democratic engagement, and social justice. The network neutrality is central to this debate since it intersects all internet layers and is related to most contemporary issues that will shape future of the internet. My assumption is that network neutrality\'s failures are not an unintended consequence of the regulatory system, but part of the problem. My core hypothesis is that network neutrality\'s limits mainly occur because of, first, its inability to secure all envisioned goals and, second, its decontextualized focus on innovation on the last mile of the internet distributional chain. The network neutrality debate has produced a wide variety of work embedded within economic and legal studies regarding what would be necessary to guarantee a free and innovative internet. Although this work has been often disguised under the mask of technique, it is widespread influenced by the evolutionary economics and denies the network neutrality's effects on ongoing struggles for social and economic justice. My proposition is that network neutrality debate has failed because it proved unable to address the problems related to concentrated power structures on the internet and increasing inequalities. To achieve this objective, this dissertation investigates the network neutrality debate over the last decades to identify processes and mechanisms by which its sterile arrangements came to take specific form in time and place, focusing on what such arrangements might inform about contemporary policy efforts. In Chapter 1, prevalent internet governance myths are deconstructed, presenting how specific architecture design and the corresponding network neutrality outcomes came to prevail in particular periods. Drawing upon and integration of distinct source materials, Chapters 2 and 3 identify the specific contingencies over the past decades by which a dynamic set of evolving actors, events, and institutions converged (or not) and gave rise to current network neutrality rules and dissent in the United States and Brazil. At the center of the analysis is the identification of structures and power struggles. Finally, Chapter 4 aims at presenting a new framework towards the network neutrality debate and its potential distributive effects in the global economy, taking technology not as deterministic but embedded and being embedded in all the building blocks of what we term the social.
Keywords: Economic power; ICT; Inequality; Innovation; Internet access; Internet governance; Law and development; Network neutrality; S&TS; Structure

Contract, Conflict and Cooperation: A Critical Analysis of the Common Law Approach to the Breakdown of Modern, Complex, Symbiotic Contracts - Soper, Charles Haward (University of Leicester, 2018)
The springboard of a real-world, doctrinal, and theoretical investigation of the role played by cooperation in complex modern contracts allows me to articulate and justify a deep and concrete Transcendent Duty to Cooperate (TDTC) for these contracts. The source of the TDTC is the express words and/or the background of such contracts, the commercial expectations of the parties; which reveal that successful performance re-quires cooperation. The inevitable inference from this is that parties implicitly agree to cooperate. As the duty is implicit, it follows, I argue, that there are no gaps to be filled; merely meaning to be unearthed from the words and/or the background (construction). In doctrinal work, I review cases in categories (prevention, facilitation, defect-rectification, communication, decision-making, and active cooperation), showing that the law is far from coherent but also far from incoherent. Shifting from judicial policy making and gap-filling to context/purpose based contract construction, using evidence, is possible and would provide coherence. I create a clear and enforceable definition of cooperation through analysing the opinions of around five-hundred commercial experts and synthesising those with doctrine and theory. My empirical work analyses experts’ views; collected by interview, an online survey and workshops, using vignettes developed from adjudicated/real-life cases including opinion on what cooperation is and how it is achieved. The findings of my survey are compared with others. At an abstract level, it aligns with comparable surveys and at a detailed level, it is unique. In theoretical work, I show that basing the TDTC on construction is superior and more efficient, brings coherence to the law and that it is underpinned by shared, normative, “community” values. I test the TDTC against various “hard” cases, analysing remedial issues, showing that it would not decrease certainty in English Commercial Law, and is defensible by an appeal for coherence.

OHADA and the Making of Transnational Commercial Law in Africa - Bashi Rudahindwa, Jonathan (Law and Development Review, 2018)
The Organisation for Harmonisation of Business Law in Africa (OHADA) was established in October 1993 with the ambitious aim of inciting economic development in its Member States. Through the adoption of Uniform Commercial Laws, the organisation is expected to create an enabling environment for business development, thereby providing for a path to economic growth and subsequent development. In light of this professed aim, both the transnational methodological approach and comparative law theories are used in this paper to critically analyse the various processes conducted under the OHADA banner and to engage in discussions on the highly debated role of law as a vehicle for development in sub-Saharan Africa. This exercise, which proves crucial in order to trace its origin within the global governance and law and development theories, allows us to present OHADA as a transnational legal system, while also highlighting both its strengths and limitations.
Keywords: Law and development; Law reform; Legislative unification; OHADA; Transnational law

Enabling intellectual property and innovation systems for South Africa's development and competitiveness - Sibanda, McLean (University of South Africa, 2018)
During the last two decades, there have been a number of policy and legislative changes in respect of South Africa’s intellectual property (IP) and the national system of innovation (NSI). In 2012, a Ministerial Review of the Science, Technology and Innovation (STI) landscape in South Africa made recommendations to improve the STI landscape and effectively the national system of innovation. The study provides a critical review of drafts of the national IP policy published in 2013 as well as the IP Framework released in 2016 for public comment. The review of the IP and the NSI are within the context of the National Development Plan (NDP), which outlines South Africa’s desired developmental goals. South Africa is part of the BRICS group of countries (Brazil, Russia, India, China and South Africa). The South African economy is characterised by a desire to move away from being dependent on resources and commodities, to becoming a more knowledge based and innovation driven economy. It is hoped that such a move would assist the country to address some of the social and economic development challenges facing South Africa, as captured in the NDP. South Africa has a functioning IP system, but its relationship with South Africa’s development trajectory is not established. More particularly, the extent to which the IP system relates to the innovation system and how these two systems must be aligned to enable South Africa to transition successfully from a country based on the production of primary resources and associated commodity-based industries to a viable knowledge-based economy is unclear. The Trade-related Aspects of Intellectual Property Rights (TRIPS Agreement) of the World Trade Organisation (WTO) provides that IP must contribute to innovation and to transfer of technology and knowledge in a manner that is conducive to social and economic welfare. Certain provisions set out the foundations of intellectual property systems within the context of each member state. This study has thus explored the complex, complementary and sometimes contested relationships between IP and innovation, with particular emphasis on the potential of an intellectual property system to stimulate innovation and foster social and economic development. The study has also analysed the interconnectivity of IP and innovation with other WTO legal instruments, taking into account South Africa’s positioning within the globalised economy and in particular the BRICS group of countries. The research involved a critical review of South Africa’s IP and innovation policies, as well as relevant legislation, instruments, infrastructure, IP and innovation landscape, and relationship with international WTO legal instruments, in addition to its performance, given the developmental priorities and the globalised economy. The research documents patenting trends by South Africans using European Patent Office (EPO), Patent Cooperation Treaty (PCT), United States Patents and Trademarks Office (USPTO) databases over the period 1996-2015. A comparative analysis of patenting trends amongst BRICS group of countries has also been documented. The study also documents new findings, observations and insights regarding South Africa’s IP and innovation systems. Some of these, particularly in relation to higher education and research institutions, are directly attributable to the Intellectual Property Rights from Publicly Financed Research and Development Act. More particularly, the public institutions are becoming relevant players in the NSI and are responsible for growth of certain technology clusters, in particular, biotechnology. At the same time, the study makes findings of a decline of private sector participation in patenting as well as R&D investment over the 20-year period. Recommendations are included regarding specific interventions to ensure coherence between the IP and innovation systems. Such coherence and alignment should strengthen the systems’ ability to stimulate innovation and foster inclusive development and competitiveness, which are relevant for addressing South Africa’s socio-economic development priorities.
Keywords: BRICS; Biopharmaceutical; Biotechnology; Commercialisation; Economic development; Flexibilities; Inclusive growth; Innovation; Intellectual property; Licensing; Patents; Start-ups; TRIPs Agreement

60 Years of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958: Are We There Yet in Sub-Saharan Africa? - Okubote, Abayomi (Social Science Research Network, 2018)
Sub-Saharan Africa has, in recent years, been classified as a natural-resource play for foreign investors. These investment potentials have made the region one of the most attractive investment destinations in the world. The region is also diverse, with a mix of different legal systems and legal traditions. While investors are constantly seeking to understand the different legal regimes, international arbitration offers comfort by providing a framework for the enforcement of rights in a neutral forum and on a different platform. According to the World Bank, the ability to enforce an arbitral award is an important factor for investors considering potential markets in which to invest.Given the sixtieth anniversary celebration of the New York Convention (NY Convention), this article examines the enforcement regimes for arbitral awards in sub-Saharan Africa. It considers the momentous developments in the enforcement regimes in the region, due to the implementation of the NY Convention. It examines the proposed amendments to the enforcement provisions in the Nigerian Arbitration Act (Repeal and Re-enactment) Bill 2017, recently passed by the Nigerian Senate. It also examines the important provisions in the revised Uniform Act on the Law of Arbitration and the revised Rules of Arbitration of the Common Court of Justice and Arbitration – both recently adopted by the OHADA Council of Ministers. It attempts a comparison between the enforcement regimes in the OHADA Member States, the NY Convention Member States, and in countries that do not belong to any of the two regimes.A chart of the legal regimes on enforcement of foreign arbitral awards in sub-Saharan Africa is attached as appendix.
Keywords: ACA; Annulment; Arbitral Awards; CCJA; Commercial Arbitration; Convention; Enforcement; Enforcement of Arbitral Awards; Foreign Awards; ICSID Convention; Judiciary; New York Convention; OHADA; Reciprocity; Reservations; Sub-Saharan Africa; Treaty; UAA; UNICTRAL Model law

A critical analysis of the removal of directors by the board of directors and the judiciary under the Companies Act 71 of 2008 - Cassim, Rehana (University of South Africa, 2018)
Section 71(3) of the Companies Act 71 of 2008 has introduced into South African company law a provision which for the first time permits the board of directors to remove another director from office in certain specific instances. A further significant innovation in the Companies Act 71 of 2008 is contained in section 162, which empowers a court to make an order declaring a director delinquent or placing him under probation in specific instances. The effect of section 162 is that a court is empowered to remove a director from the board of directors. The focus of this thesis is the removal of directors from office by the board of directors and by the judiciary. The thesis explores the underpinning philosophy of the statutory provisions relating to the removal of directors from office. It also examines the impact of the power given to the board of directors and to the courts to remove a director from office. The grounds and the procedures for the removal of directors by the board of directors and the judiciary are examined. The fiduciary duties applicable to directors in removing a director from the board of directors are also explored. In addition, this thesis examines the removal of directors holding multiple positions or capacities in relation to a company, such as an employee or a shareholder with loaded voting rights. The remedies which may be relied on by a director who has been removed from office by the board of directors are examined. Recommendations are made to strengthen and improve the provisions in the Companies Act 71 of 2008 relating to the removal of directors from office by the board of directors and the judiciary. Amendments to the Companies Act 71 of 2008 are suggested to remove ambiguities; to guard against the abuse of sections 71(3) and 162; to improve the grounds and procedures for the removal of directors by the board of directors and the judiciary, and to enhance the remedies that may be relied on by a director who has been removed from office by the board of directors.
Keywords: Corporate governance; Directors and shareholders power; Directors of corporations; Fiduciary duties; Investor relations; Removal of directors from office; Stockholders' voting; Voting rights

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

Application of the OHADA Accounting System by Companies in DRC, Current Status and Prospects: Case of the City of Bukavu - Kulondwa, Safari; Nshobole Bahirwe, Nathalie (Journal of Accounting, Finance and Auditing Studies, 2018)
The objective of this research was to determine the current status of the application of the OHADA accounting system in DRC, five years after its adoption. A survey was conducted on thirty small and medium-sized enterprises in Bukavu to determine the level of compliance with the SYSCOHADA principles, the degree of harmonization of accounting practices and the difficulties related to the application of this system. The results shown consistently that compliance with Syscohada principles is not absolute, the level of Harmonization is still low and finally companies in DRC still need time to fit into the OHADA accounting system.
Keywords: Accounting Practices; Accounting Principles; Harmonization

Cross border merger and shareholder's rights - Severino, Francesco (LUISS Guido Carli, 2018)
Historical context. Scope of application of cross border merger. A comparison of class rights with minority protection in cross border merger. The transposition of the cross border merger in the German law for an implementation.

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

The integration of work and parenting: a comparative legal analysis - Rossouw, Elzaan (Stellenbosch University, 2018)
Given the importance of parental care to children, parents and broader society and the apparent conflict between work and adequate parental care, this study evaluates the legal facilitation of the integration of work and care across nine countries, including South Africa. The study recognises that legal operationalisation of the integration of work and care primarily takes place at domestic legislative level and shows that this happens against the backdrop of widespread recognition of the importance of the family and care at the international, regional and constitutional levels. The study builds on the reality that domestic legislation in this context consists of (a combination of) equality law and specific rights contained in employment standards legislation. The comparative review of equality law as applied in the area of the work-care conflict shows that, despite the potential and promise that equality law holds to facilitate the integration of work and care, this potential has not been realised and probably will not be in future. This necessarily shifts the focus to an approach founded on the extension of specific rights related to time off or leave, as well as flexible working, to employees in order to enable them effectively to combine work and caregiving. The comparative review of specific rights in this area leads to the conclusion that South Africa lags far behind certain developed and comparable developing countries in its legislative recognition of the importance of caregiving and in its subsequent level of employment rights extended to caregivers. Given the ample room for improvement, suggestions for legislative reform are made based on the comparative experience of other countries
Keywords: Child care services; Comparative law; Employee rights; Employment standards; Equity; Labour law; Labour legislation

Does the 1980 Vienna Sales Convention Reflect Universal Values? The Use of the CISG as a Model for Law Reform and Regional Specificities - Schroeter, Ulrich (Loyola of Los Angeles International and Comparative Law Review, 2018)

African Trade Growth or Trade Deficit: GATT/WTO Rules as Trojan Horse on African Trade Development - Obida, Idibia Daniel (World Journal of Research and Review, 2018)
The principle of Most Favored Nation (MFN) as a GATT rule as annexed to World Trade Organisation (WTO) is viewed as very crucial in the operations of the WTO amongst member countries. Another rule of striking importance is the standard of non-discrimination inserted in the MFN rules. As against the background, this study addresses the routine conviction with respect to the viability of GATT laws and WTO rules in the light of non-discrimination principle and Multifibre Agreement (MFA) and, The National Treatment Principle. The study explores the standards of these rules which are whittled down with concrete exemption clauses. These clauses make the adequacy of unhindered commerce guideline perplexed amongst member nations especially, the Sub-Saharan Africa. The study finds that rules of GATT having been made since 1947 at the time when Africa‟s economic development was annexed to their colonial masters and therefore, not in contemplation by the progenitors. The realization that Africa ought to be given chance to develop come too late within the GATT rules. The study finds that the current GATT structure cannot advance the promotion of African trade. The study addresses the grouping of African nations with other nations like Asia, India and South America as a misnomer and erroneous as Africa is the least developed in terms of international trade bargaining power among other developing countries. The study after analyzing MFN, MFA, National Treatment principle and Transparency rules of GATT, concludes they are development deficit as against trade promotion. The study further concludes that the difficulties in finding an acceptable definition of the „like product‟ by several Dispute Resolution Panels as laid down by GATT makes nonsense of the rule and a lacuna in the definition of Article III (2) and III (4) as they are components of paralysis of non-clarifications.
Keywords: GATT; General Agreement on Tariffs and Trade; Most Favoured Nations; Multifibre Agreement; WTO; World Trade Organization

The Impact of Private Securities Lawsuits on Accounting Conservatism and the Moderating Influence of Corporate Governance - Kerr, Ryan (Victoria University of Wellington, 2018)
This study investigates the impact of conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit, on the level of accounting conservatism in financial reporting. This study also investigates the moderating influence of corporate governance on the level of accounting conservatism following conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit. The study uses a sample of 617 privately enforced disclosure-related securities lawsuits against listed US firms, taken under SEC rule 10b-5 of the 1934 Securities Exchange Act, over the period 2002 to 2010. The results of the study indicate that following both the conduct that gives rise to a securities lawsuit, and the filing of a securities lawsuit, firms adopt higher levels of accounting conservatism. However, the study finds no evidence that corporate governance moderates the impact of securities lawsuits on the level of accounting conservatism.
Keywords: Accounting Conservatism; Governance; Securities Lawsuits

An evaluation of market responses to corporate disclosures in a continuous disclosure environment - Li, Hanqiao (Victoria University of Wellington, 2018)
Corporate disclosure has attracted the attention of researchers from the accounting and capital markets. Researchers have been trying to better understand how capital markets respond to corporate disclosures. This study explores the short- and the long- term market effects of corporate disclosures in a continuous disclosure environment. This study aims to find the answers to the following research questions. (1) How market (price/volume) sensitive is the information contained in each disclosure category in a continuous disclosure environment? (2) How quickly is the value-relevant information incorporated into share prices before the annual earnings announcement is released, and how can company announcements promote this timeliness of price discovery? Specifically, this study examines the extent to which the Australian share market reacts to new public information immediately after the information is released, and the impacts of announcement frequency as to different continuous disclosure categories on the timeliness of price discovery (also known as the speed of price discovery). Prior research has mostly concentrated on a single type of information event to examine the information’s market consequences by monthly, weekly or daily data. Instead, by covering all public announcements and using tick (transaction) data to calculate intraday abnormal returns and abnormal trading volumes, this study examines which type of announcement has the largest immediate market responses, and compares the magnitude (with positive/negative signs) of market reactions to different announcement categories on the Australian Securities Exchange (ASX). This study is more attractive under the Australian Continuous Disclosure Regime (CDR) because of the classification system regarding the market-sensitive announcements. Whether or not an announcement is market-sensitive is predetermined by ASX ‘specialist staff’ before the announcement is released on the market. This study investigates how the market interprets the announcement, examining market sensitivity from both the share price and trading volume movements after the announcement is available to the market. In other words, to some extent, the ‘market sensitivity tag’ shows the announcement that the market should react to, and this study reveals the announcement that the market does react to. Focusing on market-sensitive announcements, except for the ASX Query, the significant results show a positive association between announcement categories and intraday Cumulative Abnormal Returns (CARs). Share prices react the most to Progress Reports and to Asset Acquisition & Disposal, and the least to Periodic Reports and Issued Capital. Share price reactions to Distribution Announcements and Other are in the middle. There are at least two possible reasons for the different market reaction magnitudes. One is the information materiality nature: if one type of information is more important to investors than other information, this may cause higher abnormal returns on the market. The other is the information predictability: if there has been a lot of relevant information available in previous days or months, share prices could adjust to the information more smoothly. In terms of the trading volume reactions, intraday Abnormal Trading Volumes (ATVs) are observed after the release of Progress Reports, Asset Acquisition & Disposal, Issued Capital and Periodic Reports. After separating good and bad news subsamples, the results show that Progress Reports and Asset Acquisition & Disposal tend to indicate good signs to the market and cause larger trading volumes. Periodic Reports and Issued Capital could contain either good or bad news, but the trading volumes are driven by bad news. The results also reveal that company size is an important factor. Large companies tend to have relatively small market responses after information is released, which confirms that the larger companies are more stable. This study also evaluates long-term market effects of corporate disclosures by examining the timeliness of price discovery (also known as the speed of price discovery). It is the timeliness with which the full value relevant information is priced over a year before the annual earnings announcement is released. Previous literature has revealed that earnings announcements convey information, because significant stock returns or increased trading volumes are observed around the time that earnings announcements are released. However, it has also been suggested that there are other more timely information sources available that contain essentially similar or even the same value-relevant information. By the time preliminary final reports become available to the market, any potential value-relevant information has been included in the share price. The CDR again provides an attractive environment to examine the impact of corporate disclosures on the timeliness of price discovery, because listed companies have to disclose to the market before any other media sources. This enables an exploration of the relationship between the timeliness and the frequency of continuous disclosures. If the CDR is efficient in keeping investors fully informed, there should be no stock price surprise after the earnings announcement is released. Given the importance of the Preliminary Final Reports to the timeliness metric and the fact that the immediate market reaction tests only cover announcements released during trading hours, this study investigates in depth the Preliminary Final Reports and finds some evidence that companies tend to release bad news after the market closes and/or on Fridays. In terms of the impacts of announcement frequency on the timeliness of price discovery, following the step ‘All announcements – Periodic/Non-periodic announcements – Detailed categories of Non-periodic announcements’, the findings reveal that only earnings-related and cash flow announcements (Periodic Reports, Distribution Announcements and Quarterly Cash Flow Reports) can accelerate the timeliness of price discovery. Unfortunately, the results do not confirm that more announcements on the market could promote the timeliness with which the value-relevant (i.e. earning/income) information is incorporated into share prices. In addition to announcement frequency influences, the price discovery process is faster for companies with better share performance, are larger or have greater profitability. Financial companies have a timelier price discovery process than other companies; the price discovery process of financial companies was affected more by the 2008 – 2010 Global Financial Crisis than that of other companies. This study contributes to the market reaction literature by covering all categories of company announcements and comparing immediate market consequences for each type of announcement, and builds upon the timeliness of the price discovery literature by linking the announcement frequency of each continuous disclosure category to the timeliness with which annual earnings information is incorporated into share prices.
Keywords: Announcement categories; Announcement frequency; Continuous Disclosure Regime; Immediate market reactions; Market sensitivity; Timeliness of price discovery

Location data and human mobility : an evaluation of a dissonance that frames data protection and privacy rights - Andrew, Jonathan (European University Institute, 2018)
With citizens’ movements mediated by many technologies that aid our navigation the potential for omnipresent surveillance may potentially institute fundamental changes to the human condition. Locational privacy is pivotal in developing inter-personal associations and relational ties with others and its function is therefore complex, rather than solely affording a degree of independence from the observations made by others. In this respect, a more nuanced understanding of the utility of location data is required; the current hierarchy that delineates personal data from special categories of personal data does not adequately appreciate the capacity for location data to act as a proxy for other sensitive personal data. Furthermore, the binary distinction that reflects the conceptualisation of the right to privacy as a negative right, with related concepts such as identity and personality formation viewed as positive constructs, is increasingly difficult a notion to preserve. The classification and terminology of technologies can illustrate how terms and legal metaphors are developed and applied so as to bridge gaps in applying existing context and precedent. Though the designation ‘location data’ once constituted a reasonable accommodation in nomenclature as an intelligible and easily comprehensible term, even while constituting a significant oversimplification of the data it represented, technological advances have rendered the term increasingly problematic. This study asks whether the existing legal framework at the regional level in Europe is apt to provide sufficiently cogent and coherent regulation given recent developments in technologies. The review analyses the risks associated with this predilection in data processing activities that allows for the identification of ever more intimate and nuanced details of a citizen’s life, behaviours and convictions through the analysis of their location data; in turn, it shall discern the necessity of considering the resulting impacts on citizens’ fundamental rights to privacy and personal data protection.
Keywords: Data Protection; European Union countries; Location data; Privacy

Analysis of the rights and duties of insurers in Nigeria - Anifalaje, K. (University of Ibadan Law Journal, 2018)
The paper analyses the rights and duties of Nigerian insurers at common law emanating from the contractual relationship between the insurer and the insured as amplified or abridged under the statute. It argues that the statutory incursion into the common law rules of uberrimae fidei, insurable interest, conditions and warranties and assignment of policies, circumscribing some of the rights exercisable by the insurer against the insured to defeat just claims as well as expanding the scope of the insurer’s duties in order to improve on service delivery is salutary. The paper, however, concludes that further reform measures, aimed at addressing some other salient issues, are still essential in the overall interest of the insuring public.
Keywords: Assurances; Assureur; Common law; Duties; Insurers; Nigeria; Rights; Statute

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (Banking in Africa, 2018)

Gaps in the IFRS Conceptual Framework - Barker, Richard; Teixeira, Alan (Accounting in Europe, 2018)
The stated purpose of the IFRS Conceptual Framework is to assist the IASB to develop Standards that are based on consistent concepts, and also to assist preparers to develop consistent accounting policies when Standards either do not apply or allow a choice of accounting policy. Yet, the Framework actually does surprisingly little to help the IASB (or preparers) determine which assets, liabilities, income and expenses should be recognised, and how they should be measured. The Framework’s focus on assets and liabilities implies that the accounting can, and should, be determined from the balance sheet. Yet, many current financial reporting requirements focus initially on the income statement, and so they are not so much derived from the Framework as instead in need of being reconciled back to it. At its heart, the problem here is that, while the Framework states that accrual accounting provides a better basis for assessing past and future performance than cash-based information, it does not explain why. To do so would require a conceptualisation of how entities’ business models are employed to create value, and of the strengths and limitations of accounting data in enhancing investors’ understanding of that value-creation. The lack of explanation of the purpose and informational objectives of accruals, how they relate to business models and how they cause the income statement and the balance sheet to interact are gaps in the Framework. Filling those gaps would provide a more robust, and natural, way for the IASB to develop recognition and measurement requirements in its Standards.
Keywords: Accruals; Conceptual framework; IFRS; Measurement; Unit of Account

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (Banking in Africa, 2018)

International norm conflicts through the lens of Alexy's principles theory - Böök, Birte (European University Institute, 2018)
The likelihood of clashes between international norms has increased in correlation with the upsurge in the number of specialised regimes emerging within the international legal field. The present thesis takes a closer look at the different ways in which such norm conflicts can be addressed at the international level. In particular, it distinguishes between conflict resolution based on establishing priority by means of traditional maxims, and resolution based on the weighing of clashing norms to determine which prevails in the case at hand. To do so, the thesis takes a step back from the existing literature and examines the distinction within norms between rules and principles, relying predominantly on Robert Alexy’s theory on this subject. Taking a legal-theoretical approach to the subject of international norm conflicts, this thesis shows that Alexy’s principles theory is not only transferrable to international law in theory, but that we can, moreover, identify international norms as rules and principles respectively. Distinguishing between the different ways in which conflicts are resolved depending on whether the norms involved are rules or principles, it is shown that while both approaches are susceptible to certain conceptual uncertainties and pitfalls, this dichotomy nevertheless plays an important role in the efficiency of the international legal system, ensuring that a certain balance between stability and flexibility is maintained. Ultimately, it is demonstrated that by viewing international law, and international norm conflicts in particular, through the lens of Alexy’s principles theory, we can gain a clearer understanding of the structure and application of international norms on the one hand and, as a result, how to resolve international norm conflicts on the other. Thus, drawing a distinction between rules and principles among international legal norms can be a means by which scholars (as well as judicial bodies or even states) may analyse ambiguous judicial decisions or international legal provisions, and can thus foster greater clarity in the field of international law.
Keywords: Dispute Resolution; International Law

An analysis of the effects of tax policy and tax abuse on the fulfilment of human rights in developing countries : the case of Zambia - Chigubu, Salome (University of Johannesburg, 2018)
Keywords: Droit fiscal; Pays en voie de développement; Politique fiscale; Tax; Zambie

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

Arbitration cost : a short comparative view of the schedule of fees of arbitration centers within the OHADA zone - Dogué, Karel Osiris Coffi (Revue de l'ERSUMA, 2018)
Amongst the seventeen OHADA member states there are over fourteen arbitration centers or institutions that handle disputes arising from contractual agreement without going through the courts of the state. The arbitration cost within the various arbitral centers differs from one arbitration center to another. The schedule or method for calculating fees are regulated by the rules of the various arbitration centers or by the OHADA Uniform Act Arbitration Rules pertaining to arbitration fees annexed to the rules of arbitration for the Common Court of Justice and Arbitration and for arbitration centers without arbitration rules. This contribution describes and contrast the various schedule of fees applicable with the arbitration centers under the OHADA zone in particular and also makes a comparative view of the arbitration fees out of the OHADA zone.
Keywords: Arbitragem; Arbitraje; Arbitration; Arbitration cost; Arbitration fee; Arbitration proceedings; Coût de l’arbitrage; Frais d’arbitrage; OHADA Arbitration's Center; Procédure arbitrale

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations

Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
Keywords: Contract; Locatio conductio

Financial Accounting: International Financial Reporting Standards - Harrison Jr., Walter T.; Horngren, Charles T.; Thomas, C. William (Bill); Tietz, Wendy M.; Suwardy, Themin (Pearson, 2018)

The fairness of forfeiture clauses in short-term insurance contracts - Huneberg, Samantha (University of Johannesburg, 2018)
Insurance fraud is a major issue in the insurance industry. Insurance companies around the world are all facing significant losses due to the prevalence of fraudulent claims. These fraudulent claims and subsequent losses suffered by insurers inevitably lead to a dilution of the insurance pool and result in other policyholders bearing the brunt of these losses. The inevitable solution for insurers is to hike the premiums for all other policyholders in order to compensate for their losses caused by fraudulent claims. Insurance fraud is an international problem and it is common for insurers in most jurisdictions to use forfeiture clauses. These clauses aim to protect the insurer by stating that if the policyholder should submit any type pf fraudulent claim, the policyholder will forfeit the entire claim. There has been much controversy around the validity and fairness of these clauses. This thesis seeks to provide an overview of the prevalence of fraudulent insurance claims in South Africa, England, Australia and New Zealand. Moreover, it will consider the fairness of forfeiture clauses in light of the fundamental movement towards policyholder protection in recent years both in South Africa and in those jurisdictions that form part of the comparative study. The thesis concludes that forfeiture clauses form an indispensable part of short-term insurance contracts and are justifiable and therefore lawful. It is, however, submitted that insurance companies have a duty to disclose the nature and extent of forfeiture clauses at the inception of the policy and again at claim stage. By using so-called staggered disclosure, insurers provide policyholders with the opportunity to consider their claim and the means with which to prove it in order to avoid instituting a fraudulent claim. The thesis recommends that these rules pertaining to staggered disclosure should form part of the 2018 Policyholder Protection Rules, together with a statutory definition of insurance fraud.
Keywords: Forfeiture; Insurance policies; South Africa

Cross-border contracting: how to draft and negotiate international commercial contracts - International Trade Centre (ITC) (International Trade Centre (ITC), 2018)
Keywords: Iinternational contracts; International sale of goods; UN Convention on Contracts for the International Sale of Goods (1980)

A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Jansen van Rensburg, Enelia Cornelia (University of Pretoria, 2018)
The use of conduit company treaty shopping structures is often regarded as an impermissible erosion of a country’s tax base. For a developing country, such as South Africa, the protection of its tax base is an important policy consideration. Arguably, one way of combatting conduit company treaty shopping structures is by including in a country’s double taxation agreements the beneficial ownership requirement set out in Article 10(2) of the OECD MTC. The study examines how a South African court would interpret this requirement in provisions in South African double taxation agreements in the context of conduit company treaty shopping involving conduit companies receiving dividends. The study firstly considers whether the beneficial ownership requirement can be regarded as an anti-avoidance rule aimed at combatting conduit company treaty shopping falling outside agents and nominee scenarios. It further considers whether the term “beneficial owner” should have a legal or economic meaning. It explores the meanings given to this term by scholars and foreign courts and the OECD in its Commentaries to the OECD MTC. The study also considers the application of the rules of interpretation contained in the Vienna Convention on the Law of Treaties when giving meaning to this term. Lastly, the study considers whether the term should have the meaning assigned to it under the domestic law of a treaty country, or under international tax law. As part of this enquiry, the meanings of the expression “beneficial owner” in South African case law and legislation are explored.
Keywords: Beneficial ownership; Conduit company treaty shopping; OECD; OECD Model Tax Convention; Société écran; South Africa

A comparative analysis of constructive dismissal in South Africa and within other international jurisdictions - Kader, Riaz (University of KwaZulu-Natal, 2018)
Abstract available in PDF.
Keywords: Constructive dismissal; Employee termination; Employees; Employers; Employment relationship; Termination of employment

Factors Influencing Indian Firms Decision Making In Foreign Direct Investment In Africa - Kukreja, Mukta; Joshi, Mahesh Chandra (International Journal of Applied Business and International Management, 2018)
India's economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the International typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.
Keywords: African nations; Developing countries; FDI; India; Indo-Afro relations; Investments; Multinational companies; OLI eclectic paradigm

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

The Organisation for the Harmonisation of Business Law in Africa (OHADA) System: Overview of some Benefits and Problem Areas - Leno, Ngaundje Doris (International Journal of Advanced Research and Publications, 2018)
As much as the Organisation for the Harmonisation of Business Law in Africa (OHADA) aims to improve the legal environment for business, the harmonisation process should be seen as a tool of economic integration with several advantages. Despite the achievements and benefits, OHADA, like other regional integration efforts in Africa, has some temporary drawbacks that may become permanent if no effort is made to overcome them. The primary focus of the paper is to present OHADA‟s background; offer an overview of some of the salient benefits of OHADA‟s institutional and regulatory framework; consider OHADA‟s problem areas; and propose possible solutions to the problems. The value of the paper, therefore, lies in the insight it offers into OHADA, the benefits and problems of its institutional and regulatory framework. It is also important because it is laying the foundation in making the OHADA structure available for all Africans.
Keywords: Business law; Harmonisation; OHADA

A comparative legal perspective on the impact of good or bad faith on the independence of documentary credits and demand guarantees - Lupton, Cayle Selwyn (University of Johannesburg, 2018)
Abstract : Please refer to full text to view abstract. LL.M. (Commercial Law)

Accounting Translation of Corporate Social and Environmental Expenditures in Small and Medium Industry: What Evaluation Approach and what Accounting Scheme? - Missomba, Jean Christian Ewane; Hanko, Osée (Research Journal of Finance and Accounting, 2018)
The question remains whether societal reporting integrates the field of financial reporting. This old debate is repeated to scrutinize the case of African companies with strong cultural roots, which do not publish alternative societal documents to traditional financial reports. Through stakeholder theory (Jones and Wicks, 1999), this study aims to analyze the phenomenon, by describing the process of accounting recordings for social and environmental information (SEI) identified by the ISO 26 000 standard in an oil Company operating within OHADA Jurisdiction. The results indicate the presence of mandatory SEIs in the financial statements, which visibility depends on the pressure exerted by the State and the accounting regulations in force. Voluntary SEIs are not visible.
Keywords: Financial reporting; ISO 26000; Social and Environmental Information (SEI); Stakeholder Theory

Some considerations on the flexibility of carrier's liability in OHBLA Law - Monkam, Cyrille (Revue de l'ERSUMA, 2018)
This article argues that the liability of the carrier is more flexible in OHBLA Transportation Law. It appears from the analysis that the carrier who is under strict or presumed liability may enjoy a large number of exemptions that may be classifiedunder classic and modern defenses on condition to act fairly and honnestly in performing the contract of carriage. The fairness and honnestly are expressed under the good faith principle. The contrary attitude -the performance in bad faith- will be sanctioned by the exclusion from the benefit of the various exemptions. The assessment of this unscrupulous behaviour of the carrier is vested on judges who have to determine in case of claims whether the behaviour constitutes a willful misconduct or a gross negligence. As examiners of the carrier's attitude, judges play a major role in establishing security and justice in contract of carriage. By setting up a flexible liability regime, the OHBLA Uniform Act is seen as a balanced instrument that sets up a compromise between carrier's interests and cargo's interests.
Keywords: Acte uniforme; Contrat de transport; Droit OHADA; Droit des transports; Transport de marchandises par route; Transportation Law

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

The protection of workers' claims in the event of the insolvency of their employer : OHADA's approach - Ngaundje, Leno Doris (Revue de l'ERSUMA, 2018)
An employer's insolvency has far-reaching consequences on workers. The consequence of business failures have complelled policy makers to provide for workers protection in the event of their employer's financial demise. The policy makers of the Organisation for the Harmonization of Busniess Law in Africa approach (OHADA) are not left out. This article seeks to examine OHADA's super-priority approach (article 95 of OHADA's Revised Insolvency Act - RIA) on the protection of workers claims with the aim of showing that approach is limited. Article 95 does not prescribe the limit on the amount protected, the time period and the category of workers concerned. This article ecognizes the need to reform article 95 of OHADA's RIA.In so doing, the article describe the position of two international bodies (International Labor Organisation -ILO) and the European Union -EU) on employee entitlements in insolvency as the bases needed to reform article 95 of OHADA's RIA. The value of this article lies in the nisights it offers into the current framework on insolvency and the opportuniy given to address the limitations that invariably arise from article 95 of OHADA's RIA.
Keywords: Droit OHADA; Faillite; Insolvabilité; Insolvency; Procédures collectives; Protection des créanciers

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Lex mercatoria in OHADA arbitration : A legal basis for unauthorized amiable composition? - Nshokano Kashironge, Dan (Bulletin ERSUMA de Pratique Professionnelle, 2018)
Keywords: Amiable composition; Arbitrage; Arbitration; Lex mercatoria; Lex mercatória

(Non) Compliance with multi-tiered dispute resolution clauses under OHADA's new ADR law : a question of juridiction or admissibility ? - Nshokano Kashironge, Dan (Bulletin ERSUMA de Pratique Professionnelle, 2018)

Corporate governance and resource management in Nigeria: a paradigm shift - Oyewunmi, Olabode Adeleke; Oyewunmi, Adebukola Esther (Business Perspectives, 2018)
The underlying significance of instituting measures for effective corporate governance and rewarding resource management outcomes cannot be relegated. The countries and organizations that deemphasize this practice have mortgaged their potential for long-term growth and corporate sustainability. This paper adopts a critical narrative method to deconstruct the essence of corporate governance and economic resource management ideals. The paper furthers the ongoing conversations on two interrelated business concepts, and provides an apt perspective towards unlocking the essence of corporate governance relative to the Nigeria’s corporate environment. It depicts a corporate paradigm shift that accommodates the dynamics of global best practices taking into account some peculiarities of Nigeria’s corporate climate. The paper also captures relevant theoretical dimensions and pragmatic policy propositions, especially for underperforming socio-economic contexts. In the light of the central theme, specific issues are discussed under the sub-headings of conceptual and theoretical clarifications, corporate governance and resource management in Nigeria, shifting the paradigms, conclusion and recommendations.
Keywords: Corporate governance; Nigeria; Resource management

Reckless and fraudulent trading by a company and the business judgment rule as a defence for directors - Peter, Lunga Cosmo (University of KwaZulu-Natal, 2018)
Abstract available in pdf.
Keywords: Business judgment rule; Company directors; Corporate governance; Fiduciary duties; Fraudulent trading; Good faith; Personal liability

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

Analysing and comparing the impact of misrepresentation and non-disclosure on the validity of a contract: similarities, differences and remedies - Ramphal, Kayra (University of KwaZulu-Natal, 2018)
This dissertation explores the concepts of non-disclosure and misrepresentation in South African law. The principal focus surrounds the effect non-disclosure as a form of misrepresentation has on the liability of contracting parties. In order to explore this effectively, the study explores the concept of duty of disclosure, and whether such a duty exists in South African law. Instances when a duty to disclose arises are explained, such as positive steps taken to conceal facts, the seller having sole knowledge of the material fact, an omission or misleading language, and a change in circumstances. Similarly to the English law duty of disclosure in relation to information in contracts uberrimae fidei, the similar South African law concept in insurance or agency contracts known as ‘utmost good faith’, is discussed and explored. The study determines whether such a concept should be a mandatory requirement in pre-contractual negotiations. Additionally, this study explores the various avenues of relief that are available to those who have fallen victim to misrepresentation. This results in an analysis of the effectiveness and success of the current traditional methods of claiming and quantifying damages that are adopted by South African legislature and the judiciary. The discussion then explores the proposed alternate method which aims to combine a claim into one of delict and that of contractual liability, or on the other hand institute a claim solely based on contractual liability. Lastly, this study explores the effect the Consumer Protection Act 68 of 2008 has had on contractual agreements, remedies and penalties, and how this ground-breaking legislation has altered the approach previously adopted by the common law and whether it has done enough to protect consumers.
Keywords: Contracting parties; Contracts; Duty to disclose; Liability; Misrepresentation; Non-disclosure

What Do Trade Agreements Really Do? - Rodrik, Dani (The Journal of Economic Perspectives, 2018)

The interconnection between express choice of forum and tacit choice of law. A comparative analysis between common-law and civil-law jurisdictions - Roux, Keegan (University of Johannesburg, 2018)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

International Trade, Environment and Sustainable Development - Ruppel, Oliver C. (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
Issues related to international trade and the environment undoubtedly are of significance to developing countries like Cameroon because they argue that developed countries have depleted resources and indulged in environmentally harmful practices during the past century, in order to achieve unprecedented high standards of living.² The developing countries therefore demand a general but differentiated responsibility, seeking open trade and compensation for adopting environmentally restraining policies.³ Upon further reflection on the link between economic growth activities, environmental protection and social development, the triangular debate on these topics will be highlighted briefly, by introducing the various perspectives.⁴ Trade creates the wealth, which

The link between reckless credit and emolument attachment orders - Singh, Nishtha (University of KwaZulu-Natal, 2018)
South Africa has experienced significant levels of reckless credit thus leading to over-indebtedness of consumers. Furthermore, research conducted in 2008 and 2013 by the University of Pretoria indicated that there were abuses prevalent in emolument attachment orders (EAOs). An interesting aspect of the research was that credit providers were particularly interested in employed consumers, as their wages or salaries were deemed to be a form of security. The aim of this dissertation is to examine the link between reckless credit and EAOs. The main research problem revolves around the fact that credit providers do not conduct thorough pre-agreement assessments and have a tendency to subscribe to the tick box approach to compliance. Moreover, these pre-agreement assessments do not make provision for the inclusion of external market factors, which is essential to safeguard consumers against economic events. This dissertation argues that, at the point when reckless credit is granted, it is inevitable that default will occur thus leading to the culmination of an EAO. In this regard, the case of University of Stellenbosch Legal Aid Clinic and Others v Minister of Justice and Correctional Services and Others; Association of Debt Recovery Agents NPC v University of Stellenbosch Legal Aid Clinic and Others; Mavava Trading 279 (Pty) Ltd and Others v University of Stellenbosch Legal Aid Clinic and Others (CCT127/15) [2016] ZACC 32 is important. The judgement illustrates how vulnerable consumers fell prey to unscrupulous credit providers who then took advantage of their salaries. An important aspect about the judgement was that section 65J of the Magistrates Court Act has now been amended through a joint interpretative mechanism of severance and reading in. The Constitutional Court’s order now requires judicial supervision in the EAO process, whereby a magistrate issues the EAO. This dissertation examines the effect of this and how EAOs are currently regulated. It also discusses whether judicial supervision is the solution to ameliorating the law on EAOs. Qualitative research methods were utilised such as legislation, case law, textbooks and journal articles. While there are no statistics to prove the link, anecdotal evidence proves the link between reckless credit and EAOs.
Keywords: Credit market; Emolument Attachment Orders; Protection of Personal Information Act; Reckless Credit

Restraint of trade clauses: does the enforcement thereof promote anti-competitive behaviour in South African law? - Sithole, Mthokozisi Wesley Nhlakanipho (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Anti-competitive behaviour; Business agreements; Competencia; Competition law; Employment agreements; Restraint of trade; Trade clause

A discussion of the success and failures of business rescue as a remedy for ailing companies - Sobantu, Vuyo (University of KwaZulu-Natal, 2018)
Companies are constantly facing risks, including financial constraints, which may contribute to companies being unable to trade in the manner desired. Unfortunately, companies that find themselves in this predicament have, in reality, been without a remedy from as early as statutory provisions regulating company law were promulgated in 1926. Judicial management, as a remedy, is notorious for being an outright failure, but the current Companies Act 71 of 2008 introduced the remedy of business rescue for financially distressed companies. The scrutiny and spotlight on the new remedy turns on whether it can be truly accessible for the companies in question and what significant changes it has made to favour financially distressed companies. This mini dissertation will aim to discuss whether the remedy of business rescue has been a success or failure.
Keywords: Ailing companies; Business rescue; Companies Act 61 of 1973; Companies Act 71 of 2008; Judicial management; South African company law; Winding up

Strict product liability in South Africa : an analysis of the concept of "defect" and the statutory defences available to the supply chain - Tennant, Sarah-lynn (University of Pretoria, 2018)
Defective products cause harm to persons and property on a daily basis. Product Liability law has accordingly evolved as a specialised area of the law of delict which seeks to prevent product accidents from happening and provides compensation in the event that defective products nevertheless reach the consumer market. Accordingly product liability regimes generally have both ex ante components such as product standards, recall mechanisms and liability provisions which are aimed at deterrence and risk-spreading as well as provisions that are applied ex post to provide redress and compensation. Designing an appropriate legal framework to underpin a product liability regime is a daunting task that involves achieving of an appropriate balance between the interests of various parties inter alia those of consumers, suppliers and the broader community. In recent decades many countries have migrated from a fault-based product liability regime to a regime which purportedly imposes strict liability on the whole supply chain. This bold move in modern product liability was pioneered in the United States who has since returned to fault-based liability for design and warning defects whilst returning strict liability in respect of manufacturing defects. After many years South Africa has joined the group of countries that applies strict liability to all defects regardless of their type. Notably the product liability regime introduced into South African law by means of the Consumer Protection Act 68 of 2008 (“CPA”) resembles the main features of the EU Product Liability Directive 85/374/EEC. The EU Model has also been taken over by Australia when they transitioned to a purportedly strict product regime in 1992. During this process the thesis also considers whether, by adopting the European model, South Africa has taken over a model which has been criticised by some American authors as outdated and based on 1965 strict product liability rhetoric as contained in section 402A of the Restatement (Second) of Torts which approach has since been discarded in the US in favour of the hybrid approach contained in the US Restatement (Third): Product Liability. This thesis focuses on product liability ex delicto. Its main aim is to interrogate and evaluate the product liability provisions contained in section 61 of the CPA, specifically with regard to the pivotal concept of defect and the statutory defences the Act has introduced. It details South Africa’s journey from the fault-based common law of product liability to the purportedly strict regime espoused by the CPA, which regimes operate parallel to each other. This is done to facilitate an understanding of the differences between the two regimes and specifically to aid interpretation and application of the product liability provisions in the CPA that deal with defectiveness and the new statutory defences. In order to obtain further guidance on how the concept of “defect” and the statutory defences in the CPA should, or could, be interpreted and applied the thesis initially considers the general foundational principles underlying product liability law and how this area of law has evolved in the United States, being the origin of modern product liability law. However, given that the South African regime of “strict” product liability ex delicto has its roots in the EU Directive and resembles some of the adapted features of the Australian product liability regime contained in the comprehensive Australian Consumer Law, the main comparative focus is on these two jurisdictions.
Keywords: Defective product; Product liability; South Africa; Supply chain

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Aspects of the taxation of company distributions in South Africa - Tredoux, Liezel Gaynor (University of Johannesburg, 2018)
As a company distribution is a means by which wealth is transferred, it is a fertile ground for tax law reform to broaden the tax base and protect South Africa against base erosion and profit shifting. The South African government has identified the corporate tax structure, and many specific corporate tax rules, as areas in South African law in need of reform, and through which the policy objectives of stimulating foreign direct investment, promoting economic growth, and creating more employment opportunities can be achieved. This study involves an analysis on two levels: the corporate tax structure; and the specific tax legislation governing company distributions in South Africa. These aspects are contrasted with comparable rules in Australia and Canada. The study also evaluates the extent to which these laws conform to the normative values of equity, efficiency, certainty, and transparency, with the aim of suggesting improvements to promote South Africa’s current policy objectives. There are a variety of design models for a corporate tax structure. In the context of distributions, the ideal design should resolve whether tax should be paid on profit earned by a company, and also be levied on a second level, on distributions made to the company’s shareholders. Certain jurisdictions merge these two levels of tax to create a single taxable event which avoids the economic double taxation of income. There is, however, no dominant or universal model and several solutions can be mooted. Australia follows an imputation system which taxes corporate income at the first level of tax but grants a tax credit to shareholders on distribution, which means this income is taxed only once. Canada applies a hybrid integration system which also combines the two levels of tax and grants a tax credit to certain individual shareholders on distribution. However, the principles applied in these two models differ. The South African corporate tax structure is a hybrid, dual-rate system in terms of which different rates apply to corporate income and distributions to shareholders. All three systems offer relief for taxpayers which partially eliminates double taxation, with Australia having eliminated it fully for resident shareholders. In broad terms, a company distribution can be made by a company to its shareholders through either a return on capital or a return of capital. The policy approach adopted by the South African government is that all net accretions of wealth by the taxpayer should be taxable. Despite government’s intentions, there is a significant difference in the taxation rules applied to returns of an income nature (dividends and income), on the one hand, and returns of a capital nature (returns of capital, distribution of assets in specie) on the other. In addition, the net accretion of wealth is not always taxable on distribution to shareholders. In most instances the tax liability in respect of the return of capital is either deferred, or alternative rules are created which deviate from the principles and immediate tax liability that apply to returns on capital (dividends and income). In certain instances this deviation is justified, but in others it could lead to inequity between taxpayers and a narrowing of the tax base – both undesirable effects. A number of proposals are made to improve the law applicable to the taxation of company distributions as regards specific transactions. These are aimed, principally, at protecting the South African tax base against base erosion and profit shifting, and aligning South Africa’s tax law with international trends. The study finds that through the application of its hybrid dual-rate corporate tax system, South Africa has reduced economic double taxation to some extent, and that it is unnecessary for South Africa to integrate company- and shareholder-level tax. In addition, a variety of changes are suggested to improve the tax legislation applicable to specific company distributions, and to promote equity, certainty, and revenue collection. The South African tax legislation regulating company distributions is, in the main, fit for purpose, although there is room for improvement when it comes to simplicity, structure, and certainty.
Keywords: Company distributions; Contributed tax capital; Corporate tax; Dividend reinvestment plans; Dividends tax; Economic double taxation; Taxation

A critical analysis on simulated transactions - Tshabalala, Alwanduxolo Thembalihle (University of KwaZulu-Natal, 2018)
No abstract provided.
Keywords: Simulated transactions; Tax avoidance; Tax evasion; Taxation

Without Silence, There Is No Golden Rule; Without Dissent, There Is No Progress - Uluc, Inan; Sutton, Kristi R. (Oregon Review of International Law, 2018)
The frequency of dissenting opinions accompanying arbitration awards in international arbitration has multiplied, particularly in international investment arbitration. Accordingly, dissenting opinions are now inevitable companions to majority awards. Notwithstanding the fact that dissenting opinions neither form part of an arbitral award nor constitute a separate award, the escalation of dissenting opinions spawns anxiety in scholars and practitioners. This trepidation ignited a crusade whereby those opposed to the practice of rendering dissent challenge the role and usefulness of these opinions. In this respect, this Article initially considers and critiques specific arguments raised by those opposed to dissenting opinions in international arbitration. Following analysis of the criticisms, this Article explores the beneficial and constructive aspects of dissenting opinions. Evident from this discussion is that dissenting opinions are not only integral to supplement an arbitrator’s quasi-judicial capacity, but also encourage issuance of well-reasoned awards. Clear from the benefits of dissenting opinions in international arbitration, any departure from the present clemency espoused toward the practice will eventuate in the field’s regression.
Keywords: Civil law; Common law; International arbitration

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims

The effects of business rescue on the companies’ stakeholders : a comparative analysis between business rescue and judicial management - Xaba, Ntombikhona Thandeka (University of KwaZulu-Natal, 2018)
Upon the recognition that the implementation of the judicial management process would not be the success that it was anticipated it would be, it became apparent that there was need for a system of corporate rescue appropriate to the needs of a modern South African economy. The legislature then introduced a new business rescue regime when the Companies Act 71 of 20082 (the Act) came into effect in the South African law. This new Act remarkably changed corporate law. One of the central features of the Act is the introduction of business rescue- a procedure which provides for the rehabilitation of financially distressed companies in a manner that seeks to balance the rights of all stakeholders. These provisions are said to be the appropriate method for modern South African economy and they differently affect the stakeholders of a company. This thesis will be discussing the different rights given to affected persons in the new Companies Act and examine how the provisions of business rescue affect different stakeholders of the company and compare such effects with those experienced under judicial management, specifically in light of the improvements of the positions of the stakeholders. Although the new business rescue is a remarkable improvement from the old judicial management system, there is still room for improvement.
Keywords: Business rescue; Companies Act 71 of 2008; Company stakeholders; Judicial management; South African company law

The Impartiality and Independence of Arbitrators and Its Implication on the Validity of Arbitral Awards - Yoga, I. Ketut Dharma Putra (Juris Gentium Law Review, 2018)
Arbitration is a way to resolve disputes outside the courts as a form of an alternative dispute resolution. The submitted dispute will be decided by one or more arbitrators, who will then render an arbitral award. One of the most fundamental principles of arbitration that must be adhered to by all arbitrators worldwide is the impartiality and independence of arbitrators, which have been regulated in various International laws. Arbitrators are not allowed to communicate with any party related to the case they are hearing. Further, arbitrators should not be influenced by others in making their decision and drafting the arbitral award to ensure objectivity and prevent any bias. An arbitrator's failure to act impartial and independent can lead to the invalidity or annulment of an arbitral award.

O.E.C.D. promotion for arbitration as an additional tool of settling disputes in the field of international taxation - Zeyen, Gaëtan (Revue de l'ERSUMA, 2018)
In a globalized world, arbitration plays an increasing role in settling international disputes. Almost all areas of Law are or might be concerned. Until very recently, [international] taxation was - as a rule - seen as a not ‘arbitrable-friendly’ matter. As the ‘classical’ method of settling international tax disputes - i.e., based on the so-called ‘Mutual Agreement Procedure’ (shortly, ‘M.A.P.’) - has shown its limits (mainly: lack of efficiency and involvement from the taxpayers themselves), arbitration became a subject of study for well-known and established academics and even an appropriate method of settling such international tax issues. As a result, both on international (O.E.C.D.) and European levels, legal initiatives have been taken, in order to promote arbitration as an additional tool of settling disputes in the field of international taxation. The purpose of the present article is, therefore, to describe and scrutinize these [very] recent legal initiatives and raise some potential issues that, at least in the author’s view, need to be addressed. One of these issues concerns the enforcement of such arbitral decisions.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration proceedings; Dispute settlement; International taxation; O.E.C.D; OCDE

A critical discussion of the directors’ duties and business judgement rule - Zondi, Sphesihle Brilliant (University of KwaZulu-Natal, 2018)
No abstract available.
Keywords: Companies Act 71 of 2008; Directors; Judgement rule; South Africa